“Mine!”: The mediating effect of trust to the role of perceived value in live selling on influencing customer purchase intention - Ang, Erika T. (Animo Repository, 2022)
Following the closure of malls and physical businesses, the pandemic drove Filipino consumers to switch to e-commerce, resulting in the emergence of live stream commerce. Since this form of commerce remains relatively new to the country, the researchers delved more into the phenomena of live stream selling to know what is the future of e-commerce here in the Philippines. As such, the study aims to determine the mediating effect of trust to the role of perceived value in live selling, particularly Utilitarian Value, Hedonic Value, and Symbolic Value on influencing customer purchase intention, and more importantly, to investigate the role of trust in products and sellers as mediating variables between perceived value and customer purchase intention in live selling. A total of 390 responses were collected, all of which were classified as users who engage and participate in live selling. The research was then carried out using SPSS (Hayes PROCESS Macro 4.0) for testing the effects and relationship of each variable with each other, together with confirmatory interviews being held afterward to cap off the research process. Thus, the analysis revealed all that dimensions of perceived value were able to produce an effect to trust and purchase intention, and more importantly, present that both Trust in Products and Trust in Sellers are able to partially mediate all the relationships between Utilitarian Value, Hedonic Value, and Symbolic Value with Purchase Intention. As such, given the results of the study, recommendations are then given for the benefit of local live sellers, business owners, and e-commerce platforms as well.